First description of the female Ozyptila kansuensis (Tang, Song & Zhu, 1995), comb. nov. (Araneae: Thomisidae) - Tang, Guo; Luo, Wei-Fen; Deng, Shu-Ye (Zootaxa, 2013)
The genus Ozyptila Simon, 1864 contains 107 catalogued species distributed mainly in the Holarctic region (Platnick 2013). This genus has traditionally been regarded as a group of small ground-living thomisids with clavate setae related to Xysticus (Lehtinen 2002). Ten species were recorded from China (Song & Zhu, 1997; Platnick 2013). Species of Ozyptila can be distinguished from those of Xysticus by the presence of clavate body setae on the abdominal dorsum, the swollen femur, and the sparsely armed leg I (Dondale & Render 1978).